Vibration Modeling and Simulation of Braced and Unbraced Steel Structure - Ratri Andinisari; Ester Priskasari; Vega Aditama; Bambang Wedyantaji; Rendy Adam Anggriawan (Journal of Infrastructure Planning and Engineering, 2023)
Repeated dynamic loads on multiple stories structure may cause damage in the midst of natural disaster, such as earthquakes and landslides, hence it is necessary to observe how the response occurs. Therefore, this paper studies the performance of two-story steel frame without braces and with inverted V concentric braces. Both frames were given a static and a dynamic load in the form of a sinusoidal load for 2 seconds in the form of forced harmonic vibration. After the dynamic load is turned off, harmonic free vibration applies. Vibration is given to the weakest orthogonal axis on the frame with a frequency of 0,5 Hz; 1,03 Hz; 1.7 Hz. To reduce the deviation between stories that occur due to dynamic loads, bracing is provided as a stiffening element. The test variations are called models 1, 2 and 3 with model 1 unbraced frame and model 2 braced frame with the same load between floors, while model 3 unbraced frame model with weight 2nd floor is 3 times larger than 1st floor. It found that the braced frame has a minimum drift and its drift is enhanced with the increase of load capacity.